Design and fabrication of A4 manual paper shredder - Mohd Shaifudin, Azmi (2007)
In this project, the main objective is to let the student make their own project based n their own idea. The study based on the manufacturing process is important to the student because it ease the student to fabricate their project. This project is about to designing and fabricating the paper shredder. This project is involves the designing process by analyzing the in-market product design. Furthermore, it can help the student on their study. After the specific design is generated, the real product can be fabricated based on the design that has been made as the guide. The main process in this project is joining using rivet and blind rivet. After the real product is done, the student will understand more about the process of designing and fabricating the product properly.